2011
DOI: 10.1128/jvi.01877-10
|View full text |Cite
|
Sign up to set email alerts
|

Herpes Simplex Virus Requires VP11/12 To Activate Src Family Kinase-Phosphoinositide 3-Kinase-Akt Signaling

Abstract: We previously showed that the herpes simplex virus 1 (HSV-1) tegument protein VP11/12 activates the lymphocyte-specific Src family kinase (SFK) Lck and is tyrosine phosphorylated in an Lck-dependent manner during T cell infection. We now extend these findings to show that ectopic expression of Lck induces robust tyrosine phosphorylation of VP11/12 in Vero cells, strongly suggesting that VP11/12 participates in an Lckmediated signaling pathway as a substrate of Lck or a kinase activated by Lck. We sought to elu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
63
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(65 citation statements)
references
References 80 publications
(87 reference statements)
2
63
0
Order By: Relevance
“…In contrast, HSV-1 Us3 suppresses both ERK and PI3K-Akt activity (33,35,36). Furthermore, specific downstream substrates such as GSK3β are regulated independent of host PI3K-Akt signaling and are, instead, directly controlled by Us3 (21,33,37,38). Here, we find that Us3 induces MT acetylation in transfected cells and is required for efficient stable MT formation in infected cells.…”
Section: Discussionmentioning
confidence: 62%
“…In contrast, HSV-1 Us3 suppresses both ERK and PI3K-Akt activity (33,35,36). Furthermore, specific downstream substrates such as GSK3β are regulated independent of host PI3K-Akt signaling and are, instead, directly controlled by Us3 (21,33,37,38). Here, we find that Us3 induces MT acetylation in transfected cells and is required for efficient stable MT formation in infected cells.…”
Section: Discussionmentioning
confidence: 62%
“…HSV also induces phosphorylation of GSK-3␣/␤ but through the US3 protein kinase (38). While HSV VP11/12 and VZV ORF12 protein both activate PI3K/Akt, HSV VP11/12 does not activate GSK-3␤ (23). In addition, while VZV ORF12 protein phosphorylates ERK and Akt, HSV VP11/12 only activates Akt.…”
Section: Discussionmentioning
confidence: 95%
“…Many viral proteins that activate the PI3K/Akt pathway either form a complex with the p85 regulatory subunit of PI3K (e.g., influenza A virus NS1 protein [24], bursal disease virus VP5 [25], HSV-1 VP11/12 [23]) or activate kinases upstream of Akt, such as Skp1 (myxoma virus M-T5 protein [26]) or Ras (EBV LMP2A [11], HSV-2 ICP10PK [27]). Some viral proteins directly associate with Akt (e.g., NS1 of influenza A virus [28], HBx protein of hepatitis B virus [29], or M-T5 protein of myxoma virus [30]).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Two tegument proteins have been shown to modulate PI3K/ Akt activity during HSV-1 infection: the US3 serine/threonine protein kinase (16) and the VP11/12 protein, encoded by the gene UL46 (17,18). Benetti and Roizman showed that HSV-1 infection leads to activation of Akt in a PI3K-dependent fashion (16), and Wagner and Smiley later showed that this effect strictly requires VP11/12 (18), a highly abundant (between 1,000 and 2,000 copies) tegument phosphoprotein (19,20).…”
mentioning
confidence: 99%